Leading change together : developing educator capacity within schools and systems - Drago-Severson, Eleanor; Blum-DeStefano, Jessica (ASCD, 2018)
This book shows how to infuse leadership, collaboration, communication, and capacity building with an understanding of individuals' experiences and capacitiesand how they influence our day-to-day work.